Butanol tolerance of carboxydotrophic bacteria isolated from manure composts - Pomaranski, Eric (Environmental technology, 2016)
Carboxydotrophic bacteria (carboxydotrophs) have the ability to uptake carbon monoxide (CO) and synthesize butanol. The aims of this study were to determine the butanol tolerance and biological production of butanol carboxydotrophic strains. In this study, 11 carboxydotrophic strains were exposed to increasing n-butanol concentrations (1-3% vol/vol) to determine their effect on growth. Butanol production by the strains was quantified and the identity of the strains was elucidated using 16S rRNA sequencing. The carboxydotrophic strains possessed inherent tolerance to butanol and tolerated up to 3% n-butanol. Among the 11 strains, T1-16, M2-32 and M3-28 were the most tolerant to butanol. The 16S rRNA gene sequence of these strains was similar (99% nucleotide similarity) to the butanol-tolerant strains Bacillus licheniformis YP1A, Pediococcus acidilacti IMUA20068 and Enterococcus faecium IMAU60169, respectively. The carboxydotrophic strains screened in this study have two distinct features: (1) high tolerance to butanol and (2) natural production of low concentration of butanol from CO, which distinguish them from other screened butanol-tolerant strains. The butanol tolerance of these carboxydotrophic strains makes them ideal for genetic studies, particularly the molecular mechanisms that enable them to survive such hostile environmental conditions and the identification of genes that confer tolerance to butanol